Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Headstone of Henry Luis Watkins (11/15/1853-12/29/1934) and his second wife "Annie" Mary Analize (1856-1919) Prospect Cemetery, west of Cleveland, TN